Oral health as a predictive factor for oral mucositis (Clinics, 2013)
OBJECTIVES: Oral mucositis is a complication frequently associated with hematopoietic stem cell transplantation, decreasing a patient's quality of life and increasing the occurrence of opportunistic infections. The purpose of this study was to determine the incidence and severity of oral mucositis and to assess the correlation of this disease with the oral health of an individual at the time of hematopoietic stem cell transplantation. METHODS: Before transplantation, patients' oral health and inflammatory conditions were determined using the gingival index and the plaque index, which are based on gingival bleeding and the presence of dental plaque, respectively. Additionally, the dental health status was determined using the decayed, missing, and filled teeth index. The monitoring of oral mucositis was based on the World Health Organization grading system and was performed for five periods: from Day 0 to D+5, from D+6 to D+10, from D+11 to D+15, from D+16 to D+20, and from D+21 to D+30. RESULTS: A total of 97 patients (56% male and 44% female) who underwent hematopoietic stem cell transplantation at the Hospital das Clinicas da Faculdade de Medicina da Universidade de Sao Paulo between January 2008 and July 2009 were prospectively examined. The incidence of ulcerative mucositis was highest from days +6 to +10 and from days +11 to +15 in the patients who underwent autologous and allogeneic hematopoietic stem cell transplantation, respectively. CONCLUSION: The data, including the dental plaque and periodontal status data, showed that these oral health factors were predictive of the incidence and severity of oral mucositis in a cohort of patients with similar conditioning regimens before hematopoietic stem cell transplantation.